Aquachlorido{μ-6,6′-diethoxy-2,2′-[1,2-phenylenebis(nitrilomethylidyne)]diphenolato}copper(II)sodium(I) N,N-dimethylformamide solvate - Ma, Xiao-Jian (International Union of Crystallography, 2009)
In the heterometallic dinuclear title compound, [CuNa(C(24)H(22)N(2)O(4))Cl(H(2)O)]·C(3)H(7)NO, the Cu(II) ion is coordinated in a square-planar geometry by two N atoms and two O atoms of the 6,6′-diethoxy-2,2′-[1,2-phenylenebis(nitrilomethylidyne)]diphenolate ligand. The Na(I) ion is hexacoordinated by four O atoms of the ligand, defining the equatorial plan, and by one O atom of the water molecule and one Cl atom occuping axial positions. The Cu(II) and Na(I) ions are bridged by two phenolate O atoms.